2016
DOI: 10.1027/1016-9040/a000243
|View full text |Cite
|
Sign up to set email alerts
|

Real Person Interaction in Visual Attention Research

Abstract: 2An important development in cognitive psychology in the past decade has been the examination of visual attention during real social interaction. This contrasts traditional laboratory studies of attention, including 'social attention', in which observers perform tasks alone. In this review we show that although the lone-observer method has been central to attention research, real-person interaction paradigms have not only uncovered the processes that occur during 'joint attention' but have also revealed attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 93 publications
0
26
2
Order By: Relevance
“…The current study suggests that there is an interaction between top-down and bottom-up mechanisms influencing social attention, but that the topdown component might only take effect in sufficiently realistic paradigms (see also [56]). Although the current study does not maximize lifelikeness to the same extent as other studies where the gaze cues are sent by a real human actor sitting opposite of the participant (e.g., [57]), it indicates that a certain level of lifelikeness needs to be reached before various context factors start modulating social attention. Where exactly this level is located and whether different context factors require different levels of lifelikeness should be the focus of future studies.…”
Section: Discussioncontrasting
confidence: 88%
“…The current study suggests that there is an interaction between top-down and bottom-up mechanisms influencing social attention, but that the topdown component might only take effect in sufficiently realistic paradigms (see also [56]). Although the current study does not maximize lifelikeness to the same extent as other studies where the gaze cues are sent by a real human actor sitting opposite of the participant (e.g., [57]), it indicates that a certain level of lifelikeness needs to be reached before various context factors start modulating social attention. Where exactly this level is located and whether different context factors require different levels of lifelikeness should be the focus of future studies.…”
Section: Discussioncontrasting
confidence: 88%
“…It is an open question whether interpretation of the visualized gaze positions as collaborative behavior underlies the collaboration benefits found in our study when making use of the shared gaze information, or if the visualized dwell locations are simply used as a spatial pointer that guides searchers as to where to search (cf. Cole, Skarratt, & Kuhn, 2016). While our findings suggest that the degree of collaboration exhibited by a search partner can be judged from the shared gaze marker, this does not indicate what extent of interpretation of the gaze marker is necessary to guide search behavior.…”
Section: Implications Of Findingscontrasting
confidence: 69%
“…Nevertheless, additional studies are necessary to further explore the link between attention holding for eyegaze stimuli and oculomotor dynamics. This could be done through paradigms that employ gaze-based interactions with pictorial faces and avatars (for reviews, see Hamilton 2016; Pfeiffer et al 2013; see also Dalmaso et al 2016;Edwards et al 2015;Pfeiffer et al 2012;Vernetti et al 2017) or even with live confederates (see Cole et al 2016;Hietanen et al 2016;Lachat et al 2012), to increase the ecological validity which is crucial for a full comprehension of social attention abilities (see Risko et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Hietanen et al (2016) explained their results by suggesting that the increased autonomic activation, that is generally observed in the presence of live direct-gaze faces (see Conty et al 2016), may have predisposed participants to react more readily to target onset. Interestingly, evidence is accumulating showing that real social interactions can shape attention in a peculiar manner as compared to pictorial stimuli (for a review, see Cole et al 2016). For instance, Gallup et al (2012) observed that pedestrians tended to shift attention more strongly in response to the spatial cues provided by live individuals observed from behind (i.e., eyegaze cues were precluded) rather than from the front, a result that contrasts with laboratory-based studies that highlighted the relevance of others' gaze stimuli for guiding attention (e.g., Emery 2000;Frischen et al 2007).…”
Section: Abstract Visual Attention • Eye Movements • Scaccadic Peak Vmentioning
confidence: 99%